2017
DOI: 10.1186/s13054-017-1687-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of acute respiratory distress syndrome in university and non-university hospitals in Germany

Abstract: BackgroundThis study investigates differences in treatment and outcome of ventilated patients with acute respiratory distress syndrome (ARDS) between university and non-university hospitals in Germany.MethodsThis subanalysis of a prospective, observational cohort study was performed to identify independent risk factors for mortality by examining: baseline factors, ventilator settings (e.g., driving pressure), complications, and care settings—for example, case volume of ventilated patients, size/type of intensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 36 publications
1
32
0
4
Order By: Relevance
“…In this study the majority of ARDS patients (85%) were transported to ARDS/ECMO centers for further treatment. Patients with a severe ARDS and potentially reversible respiratory failure may have a better chance to survive when transported to an ECMO center [1719]. …”
Section: Discussionmentioning
confidence: 99%
“…In this study the majority of ARDS patients (85%) were transported to ARDS/ECMO centers for further treatment. Patients with a severe ARDS and potentially reversible respiratory failure may have a better chance to survive when transported to an ECMO center [1719]. …”
Section: Discussionmentioning
confidence: 99%
“…The ARDSnet Low Vt (LVt) method is intended to protect the non-dependent normal lung tissue from overdistension (OD) and reduce alveolar recruitment/ derecruitment (R/D) with positive end expiratory pressure (PEEP), while resting severely injured tissue by allowing it to remain collapsed throughout the ventilation cycle [2]. However, this strategy has not further reduced ARDS mortality [1,[3][4][5][6][7][8][9][10][11]. This suggests that our understanding of ARDS pathophysiology remains [12] all using the airway pressure release ventilation (APRV) mode but with different methods: a Stock et al used a CPAP phase that encompassed 60% of each breath, a release phase of 1.27 s and a respiratory rate (RR) of 20/min [98]; b Davis et al decreased the respiratory rate by prolonging both the CPAP and release phase [99]; c Gama de Abreau et al adjusted their CPAP and release phase to values typical of a conventional breath [100]; d Roy et al minimized the release phase and extended CPAP to occupy 90% of each breath, typical of the time-controlled adaptive ventilation (TCAV) method [83].…”
Section: Protect and Rest Strategymentioning
confidence: 99%
“…The current understanding is that open and collapsed tissues are not delineated into compartments, but are rather intermingled throughout the entire lung [17][18][19][20][21]. The unchanged mortality associated with the LVt method may also reflect the fact that maintaining lung tissue collapse ("resting") may not be protective [1,[3][4][5][6][7][8][9][10][11]. The atelectatic lung does not exchange gas, is susceptible to pneumonia, and may ultimately lead to collapse induration and fibrosis with the inability to re-inflate or epithelialize the airspace [22][23][24].…”
Section: Protect and Rest Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…It was not until the ARDS Network (ARDSnet) conducted the seminal ARMA study, published in 2000, that a reduction in mortality was shown (Acute Respiratory Distress Syndrome Network, 2000). However, most (Phua et al, 2009;Villar et al, 2011;Caser et al, 2014;Bellani et al, 2016;Laffey et al, 2016;Villar et al, 2016;Maca et al, 2017;Raymondos et al, 2017;Rezoagli et al, 2017;Fan et al, 2018;McNicholas et al, 2018;Pham et al, 2019;Shen et al, 2019) but not all (Brun-Buisson et al, 2004;Fan et al, 2005;Putensen et al, 2009;Petrucci and De Feo, 2013;Shen et al, 2019) of the recent statistical-and meta-analyses have shown that ARDS mortality has not been reduced below the 31% "gold standard" of the 2000 ARMA study but rather remains unacceptably high at ∼40% (Figure 1). Despite these disappointing results, the low-Vt ARDSnet method is still recommended as the standard-of-care protective ventilation strategy for ARDS patients (Fan et al, 2017(Fan et al, , 2018Papazian et al, 2019).…”
Section: Introductionmentioning
confidence: 99%